IMPLEMENTASI PARLIAMENTARY THRESHOLD DALAM PEMILIHAN ANGGOTA DPRD PROVINSI DAN DPRD KABUPATEN/KOTA - Fatih, Sholahuddin al (IAIN Tulungagung, 2018)
Indonesia has held election since 1955. In several periods of election, there were changes of regulation. One of them is about Parliamentary Threshold. As known, Parliamentary Threshold has been applied in Indonesia in elections period of 2009 by 2.5%. In the 2014 elections, parliamentary threshold changed into 3.5% and did not apply nationally. In accordance to the mandate of the Constitutional Court Decision Number 52/PUU-X/2012, the parliamentary threshold applies only to count the number of a legitimate votes political party in the House of Representative (DPR). In election period of 2019, Parliamentary Threshold was increased to 4% and applies only to count the number of a legitimate votes political party in the House of Representative (DPR).Thus, at the level for Local House of Representative of Provincial DPRD and Regency/City DPRD shall not apply the provisions of the Parliamentary Threshold. This situation led to many political parties to parliament, which can be ineffectiveness of local government performance. Therefore, it is necessary to simulate Parliamentary Threshold to apply equitable parliamentary electionsÂ in Provincial DPRD and Regency/City DPRD and also the fair percentage of Parliamentary Threshold to create effective governance performance and simple multi-party system in region.Keywords: Implementation, Parliamentary Threshold, Election for Members of Provincial DPRD and Regency/City DPRD